Customer Loyalty in E-Banking Across Generations - Jakóbik, Karolina; Wójtowicz, Tomasz; Suder, Marcin (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
This article aims to identify the differences in customer loyalty among generational groups in the context of electronic banking. The study is based on a survey that was conducted among 321 Polish respondents. Using correspondence analysis and chi-square tests, we confirmed statistically significant generational differences in loyalty; Generation Z showed the lowest loyalty levels, while Baby Boomers displayed the highest. By applying correspondence analysis – a rarely used method in this context – we revealed distinct loyalty patterns that were linked to generational traits. The findings suggest that banks should adopt age-differentiated loyalty strategies. For younger customers (particularly Millennials and Generation Z), personalised digital experiences, alignments with brand values, and emotional engagement may be key to improving their loyalty. In contrast, emphasising service reliability, long-term trust, and security is likely to be more effective for older generations such as Generation X and Baby Boomers. This study enhances both a theoretical understanding and practical strategies for customer retention in e-banking.